Use of Test-Teach-Test Method in English as a Foreign Language Classes - Paudel, Pitmbar (Journal of NELTA Surkhet, 2018)
The present study 'Use of test-teach-test method in EFL classes' aims to find out the effect of teach-test-teach method in developing vocabulary, grammatical and reading comprehension skills of Bachelor level first year EFL students in the faculty of education, Tribhuvan University, Nepal. For this experimental research, the sample population consisted 42 B. Ed. students from a Public College, Pokhara who were selected using purposive non-random sampling procedure. The students were divided into two groups; experimental and controlled; each consisted 21 students on the basis of odd even ranking system. The main tools for data collection were test items. A pre-test was administered before they were taught for 4 weeks. Then, the experimental group was taught using test-teach-test method. After experimental teaching, post-test was administered by using the same set as that was used in pre-test. The results of both the tests were compared and determined using simple statistical tool; mean. The findings revealed that the experimental group was found to be performed significantly higher than controlled group.Journal of NELTA Surkhet Vol. 5 January, 2018, Page: 15-27